Commissioning of a well type chamber for HDR and LDR brachytherapy applications: a review of methodology and outcomes - Mukwada, Godfrey; Neveri, Gabor; Alkhatib, Zaid; Waterhouse, David K.; Ebert, Martin (Australasian physical & engineering sciences in medicine, 2016)
For safe and accurate dose delivery in brachytherapy, associated equipment is subject to commissioning and ongoing quality assurance (QA). Many centres depend on the use of a well-type chamber (‘well chamber’) for performing brachytherapy dosimetry. Documentation of well chamber commissioning is scarce despite the important role the chamber plays in the whole brachytherapy QA process. An extensive and structured commissioning of the HDR 1000 plus well chamber (Standard Imaging Inc, Middleton WI) for HDR and LDR dosimetry was undertaken at Sir Charles Gairdner Hospital. The methodology and outcomes of this commissioning is documented and presented as a guideline to others involved in brachytherapy. The commissioning tests described include mechanical integrity, leakage current, directional dependence, response, length of uniform response, the influence of insert holders, ion collection efficiency, polarity effect, accuracy of measured air kerma strength ( S K ) or reference air kerma rate ( K R ) and baseline setting (for ongoing constancy checks). For the HDR 1000 plus well chamber, some of the insert holders modify the response curve. The measured sweet length was 2.5 cm which is within 0.5 % of that specified by the manufacturer. Correction for polarity was negligible (0.9999) and ion recombination was small (0.9994). Directional dependence was small (less than 0.2 %) and leakage current was negligible. The measured K R for 192 Ir agreed within 0.11 % compared with a second well chamber of similar model and was within 0.5 % of that determined via a free-in-air measurement method. Routine constancy checks over a year agreed with the baseline within 0.4 %.